Swallowing difficulties in the elderly: caregiving needs and responsibilities for elderly residing in care homes - Lakhi, Saleha Y. (My University, 2023)
Introduction: The prevalence of swallowing difficulties in the elderly appears to be significantly high within care homes, but there is a dearth of information regarding caregiving needs within this context, especially from a South African perspective. South Africa’s burden of disease, the growing elderly population, and a growing focus on optimising elderly care confirm the need for research within this area. Rationale: There is a paucity of literature on the perspectives of caregivers working with elderly individuals in residential care facilities relating to their experiences, responsibilities, facilitators and challenges to service provision and providing optimal care to their residents, specifically at mealtime and pill-swallowing routines. Since speech-language pathologists are essential in evaluating and managing swallowing difficulties, they are in an optimal position to provide support to caregivers to encourage the best level of care in residents with swallowing impairments, should it be required. This research served to fill in the gaps in the literature regarding services to the elderly population residing in care homes and explored the needs that may be present in this context from the view of the caregiver. Methodology: The aims of this study were to: 1) To describe the experiences and practices of caregivers with elderly residents during mealtimes at care homes, 2)To describe the difficulties experienced by residents of the care home during mealtimes and pill-swallowing routines, as viewed by the caregiver and 3)To describe caregivers’ perspectives on training and support needs for mealtimes and pill-swallowing routines with caregivers. To explore these aims, a qualitative study was conducted with data collection consisting of three phases namely observations, focus groups, and interviews. Observations were conducted over a period of two weeks at two research sites in Gauteng followed by two focus groups, one at each site. Thereafter, interviews were held with seventeen participants who were selected through purposive sampling. Data Analysis: Data was analysed inductively using Braun and Clarke’s Thematic Analysis Procedure. Interviews were transcribed and then coded using Microsoft Excel and five primary themes were derived from analysis of the interviews and focus groups. Observations were recorded through field notes. Results: Five themes emerged from the study: a) Barriers and facilitators to mealtime experience, b)Management strategies utilised during mealtimes, c) Description of the difficulties observed by caregivers, d) Caregivers’ involvement in medicine administration, and e) Perspectives on training and support needs. Caregivers experienced various facilitators and barriers including resident characteristics such as resident temperaments and comorbid condition, caregiver characteristics such as years of experience. Caregivers observed a range of difficulties in residents during mealtimes and pill-swallowing routines and various management techniques tailored to individual residents were utilised to facilitate efficiency during mealtimes. It is not within the scope of practice for caregivers who aren’t professional nurses to administer medicines however these caregivers were involved in pill-swallowing routines with residents. Caregivers shared their perspectives on training needs and identified topics requiring further training such as, management of non-compliant residents and the effects of various medical diagnoses on swallowing in the care home context. Implications: Findings from this study suggests that further research is required investigating the possible role of caregivers who aren’t qualified to administer pills but may still be involved in pill-swallowing routines in the care home settings. This study identified a range of barriers to mealtimes and pill-swallowing routines as perceived by caregivers which would need to be addressed through training, workshops, and the formulation of policies by relevant stakeholders.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Arts in Speech Pathology to the Faculty of Humanities, University of the Witwatersrand, 2023
Keywords: Caregiver; Swallowing; Elderly care homes